Stable Density and Dynamics of Dendritic Spines of Cortical Neurons Across the Estrous Cycle While Expressing Differential Levels of Sensory-Evoked Plasticity - Alexander, Bailin H.; Barnes, Heather M.; Trimmer, Emma; Davidson, Andrew M.; Ogola, Benard O.; Lindsey, Sarah H.; Mostany, Ricardo (Frontiers in Molecular Neuroscience, 2018)
Periodic oscillations of gonadal hormone levels during the estrous cycle exert effects on the female brain, impacting cognition and behavior. While previous research suggests that changes in hormone levels across the cycle affect dendritic spine dynamics in the hippocampus, little is known about the effects on cortical dendritic spines and previous studies showed contradictory results. In this in vivo imaging study we investigated the impact of the estrous cycle on the density and dynamics of dendritic spines of pyramidal neurons in the primary somatosensory cortex of mice. We also examined if the induction of synaptic plasticity during proestrus, estrus, and metestrus/diestrus had differential effects on the degree of remodeling of synapses in this brain area. We used chronic two-photon excitation microscopy during steady-state conditions and after evoking synaptic plasticity by whisker stimulation at the different stages of the cycle. We imaged apical dendritic tufts of layer 5 pyramidal neurons of naturally cycling virgin young female mice. Spine density, turnover rate, survival fraction, morphology, and volume of mushroom spines remained unaltered across the estrous cycle, and the values of these parameters were comparable with those of young male mice. However, while whisker stimulation of female mice during proestrus and estrus resulted in increases in the turnover rate of spines (74.2±14.9% and 75.1±12.7% vs. baseline, respectively), sensory-evoked plasticity was significantly lower during metestrus/diestrus (32.3±12.8%). In males, whisker stimulation produced 46.5±20% increase in turnover rate compared with baseline – not significantly different from female mice at any stage of the cycle. These results indicate that, while steady-state density and dynamics of dendritic spines of layer 5 pyramidal neurons in the primary somatosensory cortex of female mice are constant during the estrous cycle, the susceptibility of these neurons to sensory-evoked structural plasticity may be dependent on the stage of the cycle. Since dendritic spines are more plastic during proestrus and estrus than during metestrus/diestrus, certain stages of the cycle could be more suitable for forms of memory requiring de novo formation and elimination of spines and other stages for forms of memory where retention and/or repurposing of already existing synaptic connections is more pertinent.